2020
DOI: 10.3390/min10030205
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of Uraninite Revisited

Abstract: Identification of uraninite provenance for the purpose of nuclear forensics requires a multifaceted approach. Various geochemical signatures, such as chondrite normalized rare earth element patterns, help identify and limit the potential sources of uraninite based on the geological setting of the uranium ore mineralization. The inclusion of accurate age determinations to discriminate geochemical signatures for natural uranium ores may help to potentially restrict geographical areas for provenance consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…206 Pb and 207 Pb are the stable daughter products from the radioactive decay of 238 U and 235 U, respectively, whereas 208 Pb is produced from 232 Th decay. The rapid determination of accurate secondary isochron Pb-Pb ages for nuclear materials, such as uraninite, is an effective nuclear forensic tool for deciphering a sample's provenance (e.g., [16]). Traditionally, secondary Pb-Pb isochron dating of geological materials and minerals involves a labor-intensive procedure that includes sample digestion, which is then followed by separation of Pb using ion exchange chromatography; the whole process can take several weeks to complete (e.g., [17]).…”
mentioning
confidence: 99%
“…206 Pb and 207 Pb are the stable daughter products from the radioactive decay of 238 U and 235 U, respectively, whereas 208 Pb is produced from 232 Th decay. The rapid determination of accurate secondary isochron Pb-Pb ages for nuclear materials, such as uraninite, is an effective nuclear forensic tool for deciphering a sample's provenance (e.g., [16]). Traditionally, secondary Pb-Pb isochron dating of geological materials and minerals involves a labor-intensive procedure that includes sample digestion, which is then followed by separation of Pb using ion exchange chromatography; the whole process can take several weeks to complete (e.g., [17]).…”
mentioning
confidence: 99%
“…The degree of similarity was quantified using the slope and the correlation coefficient of a linear regression approach. The formation age of uranium ore deposits differs significantly, which allows for researchers to use the Pb isotope composition to identify or confirm the origin of uranium ore samples [70]. Recently, Corcoran et al [71] presented a combination of geochemistry, isotopic composition, and mineralogy using PCA to separate different uranium ore deposit types, which can be used as an APO if applied to an uranium ore sample in question.…”
Section: Uranium Ores and Productsmentioning
confidence: 99%
“…In addition, some fluids were mobilized via a hydrothermal effect of granites from the surrounding Lower Paleozoic metasediments. A number of published works have shown that uraninite is sensitive to subsequent post-mineralization processes (e.g., [57][58][59][60][61][62][63]), which are also reflected in the results of dating. From this point of view, the younger age of uraninite obtained from the U-REE-bearing quartz-fluorapatite vein atČučma by Števko et al [10] (Figure 14) reflect subsequent, Paleoalpine processes and might represent a younger, remobilized generation of uraninite, although the whole mineralization is also originally related to S-type granitic magmatism.…”
Section: Genesis and Age Of U-mo Mineralizationmentioning
confidence: 99%